ANALISIS EKSISTENSI PRODUK INVESTASI SYARIAH DALAM PLATFORM FINTECH DI INDONESIA (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
ABSTRACTFinancial technology (fintech) has revolutionized the financial sector as a whole. This technological innovation allows people to access financial services more easily and quickly, one of which is through sharia-based digital investment. This study aims to determine sharia investment products in the fintech platform, the legal basis for technology-based sharia investment (fintech), and the opportunities and challenges of technology-based sharia investment products (fintech) in Indonesia. The method used in this study is a descriptive method by applying a qualitative approach. The results of this study show that sharia investment products available on digital platforms include several financial instruments such as sharia stocks available on the Ajaib platform, sharia mutual funds available on the Bareksa platform, and sukuk (sharia bonds) available on the Investree platform. In running its operational system, the legal basis used in technology-based sharia investment products is POJK Number 77 of 2016 concerning Information Technology-Based Money Lending Services, PBI Number 19 of 2017 concerning Financial Technology Providers, and DSN-MUI fatwa Number 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services based on Sharia Principles. As a new innovation, technology-based sharia investment products have several opportunities and challenges in their implementation. These opportunities include wide accessibility, operational cost efficiency, and conditions where the majority of Indonesia's population is Muslim. The challenges faced are the absence of clear and comprehensive regulations, public knowledge about sharia transaction contracts and sharia fintech operational mechanisms that are still minimal, and limited internet access and digital infrastructure.